Independent contracting : succeeding as a contract professional in Australia - Green, Ruth.; Petty, John.; Woodd, Janet.; Robinson, Kate. (Pearson Education, 2000)
This book is about: Taking the plunge; Legal identity; Business identity; Financing your business; Attracting clients; Getting the contract right; ...